(untitled) (Journal of Geography and Environmental Management, 2018)
The organization of leisure of children is the most actual problem today. By means of tourism, it is possible to give to younger generation the chance for increasingtheir intellectual level, development of observation, skill to communicate, self-discipline, adaptation to conditions of modern life, ability to perceive beauty of the world around.Children’s tourism is an effective mean of education, training, rehabilitation, formation of the personality of children, adoption of a healthy lifestyle. There are all conditions for the development of this type of tourism in Kazakhstan. The article discusses the features of the children’s organization of tourism in Kazakhstan. Analyzed children’s tourism market in the country developed a classification of school camps, as well as the possibilities of opening the center of youth tourism, dealing with the organization of tourist-sports, sightseeing and local history activities.